SYNTACTIC FEATURES OF MODERN UZBEK MEDIA LANGUAGE - Akhmedovich, Gaffarov Alisher (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the syntactic transformation of contemporary Uzbek media language under the influence of digital journalism, focusing on how sentence structure, stylistic choices, and linguistic functions have evolved in response to online communication trends. Method: A descriptive and comparative analysis was conducted on texts from leading Uzbek media outlets (Kun.uz and Daryo.uz) and social media news posts to identify syntactic tendencies. Results: The findings reveal significant structural changes, including sentential reduction, increased parataxis, and frequent use of elliptical constructions, reflecting a shift toward brevity, readability, and immediacy. Contemporary Uzbek media language demonstrates hybrid syntax, merging formal written and informal spoken elements, which caters to the digital audience’s preference for concise and transparent communication. Novelty: This study provides the first systematic account of how digital transformation reshapes the syntax of Uzbek media language, positioning these linguistic adaptations as a reflection of the broader technological and communicative shifts defining modern journalism in the digital era.